An analysis of the experimental and theoretical charge density distributions of the piroxicam–saccharin co-crystal and its constituents. Issue 85 (30th August 2016) - Du, Jonathan J.; Váradi, Linda; Williams, Peter A.; Groundwater, Paul W.; Overgaard, Jacob; Platts, James A.; Hibbs, David E.
Abstract : Experimental and theoretical charge density of piroxicam, saccharin and their 1 : 1 co-crystal have been determined using high-resolution X-ray diffraction, multipole refinement and DFT calculations Abstract : Experimental and theoretical charge density analyses of piroxicam (1 ), saccharin (2 ) and their 1 : 1 co-crystal complex (3 ) have been carried out. Electron density distribution (EDD) was determined through the use of high-resolution single crystal X-ray diffraction and the data were modelled using the conventional multipole model of electron density according to the Hansen–Coppens formalism. A method for optimising the core density refinement of sulfur atoms is discussed, with emphasis on the reduction of residual electron density that is typically associated with this atom. The asymmetric unit of complex (3 ) contains single molecules of saccharin and the zwitterionic form of piroxicam. These are held together by weak interactions (hydrogen bonds, π–π and van der Waals interactions), ranging in strength from 4 to 160 kJ mol −1, working together to stabilise the complex; analysis of the molecular electrostatic potential (MEP) of the complexes showed electron redistribution within the co-crystal, facilitating the formation of these generally weak interactions. Interestingly, in the zwitterionic form of piroxicam, the charge distribution reveals that the positive and negative charges are not associated with the formal charges normally associated with this description, but are distributed over adjacent molecular fragments. The use of anisotropic displacement parameters (ADPs) for hydrogen atoms in the multipole model was also investigated but no improvement in the quality of the topological analysis was found.